2013
DOI: 10.4103/0300-1652.114583
|View full text |Cite
|
Sign up to set email alerts
|

Association of Helicobacter pylori infection with the Lewis and ABO blood groups in dyspeptic patients

Abstract: Background:Helicobacter pylori infection is a basic risk factor for chronic gastritis, and gastric carcinoma. Based on some studies, the reason is binding of H. pylori to H and Leb antigens in gastric mucosa. However, some other findings have not determined any association between the infection and these antigens. Because of this controversy and the fact that H. pylori infection and gastric adenocarcinoma are common diseases in Iran, the assessment of the association of H. pylori infection with these blood gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
1
10
1
Order By: Relevance
“…In contrast, our finding was higher than other results reported from Ethiopia; 49 – 70% in Bahirdar [ 20 ], 56 – 70%) in Addis Ababa [ 25 , 26 ] and 66% in Gondar [ 27 ]. Also, the present result was found to be lower than the figures reported in Iran (46.6 – 64.8%) [ 18 , 28 , 29 ], Turkey (68%) [ 21 ], and in Portugal City of Coimbra (67%) [ 19 ]. The higher prevalence of H. pylori infection may be related to poor personal hygiene, low standard of living and low economic status among dyspeptic patients in the study area.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…In contrast, our finding was higher than other results reported from Ethiopia; 49 – 70% in Bahirdar [ 20 ], 56 – 70%) in Addis Ababa [ 25 , 26 ] and 66% in Gondar [ 27 ]. Also, the present result was found to be lower than the figures reported in Iran (46.6 – 64.8%) [ 18 , 28 , 29 ], Turkey (68%) [ 21 ], and in Portugal City of Coimbra (67%) [ 19 ]. The higher prevalence of H. pylori infection may be related to poor personal hygiene, low standard of living and low economic status among dyspeptic patients in the study area.…”
Section: Discussioncontrasting
confidence: 92%
“…As to the relation between ABO blood group and H. pylori infection, contrasting evidences exists in which some studies revealed the presence of association [ 17 – 19 ], while others not [ 2 , 20 – 22 , 24 , 29 ]. Similar to the latter groups, we observed neither ABO nor Rh was significantly associated with infection in our study population, which challenges reports indicating participants with blood type O are more prone to H. pylori infection.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 8 , 9 In contrast, other researchers could find no association between the ABO blood groups and H. pylori infection among an adult population in Mashhad, Iran. 13 , 14 However, both studies were carried in the same locality, a thing that might raise the possibility regarding an influencing effect of genetics of the group to the outcome, another plausible explanation could be the existence of different H. pylori strains in that locality as it has been documented by different studies that the different strains are not equally specific for O group. 27 , 28 Moreover, they used the urea breath test in one of the two studies, while they used antibody testing for H. pylori in the other study.…”
Section: Discussionmentioning
confidence: 99%
“…One of the genetic risk factors is the expression of ABO blood group phenotypes in different people (11,12). These bacteria identify and bind to blood group antigens expressed on the surface of gastric mucosa and play an important role in the stability of infection (13,14). During colonization, H. pylori in the stomach bind to Lewis's antigens and type 1 antigen of the gastric mucosa.…”
Section: Introductionmentioning
confidence: 99%